2016
DOI: 10.1016/j.conbuildmat.2016.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the climate impact effects of increased use of bio-based materials in buildings

Abstract: Whenever Life Cycle Assessment (LCA) is used to assess the climate impact of buildings, those with high content of biobased materials result with the lowest impact.Traditional approaches to LCA fail to capture aspects such as biogenic carbon exchanges, their timing and the effects from carbon storage. This paper explores a prospective increase of biobased materials in Swedish buildings, using traditional and dynamic LCA to assess the climate impact effects of this increase. Three alternative designs are analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(70 citation statements)
references
References 20 publications
0
53
0
4
Order By: Relevance
“…One such example is mandatory use of timber frames. Although substituting timber for concrete is usually beneficial in terms of climate change impact (Peñaloza, Erlandsson, & Falk, 2016;Salazar & Meil, 2009), concrete could conceivably be a better solution in cases where it is produced with a low clinker content or carbon storage techniques (De Schepper, Van den Heede, Van Driessche, & De Belie, 2014;Razi, Razak, & Khalid, 2016). On the other hand, performance requirements allow for flexibility and innovation and ensure that the desired outcome is reached, but their implementation and monitoring often require dedicated software, staff training or third party experts.…”
mentioning
confidence: 99%
“…One such example is mandatory use of timber frames. Although substituting timber for concrete is usually beneficial in terms of climate change impact (Peñaloza, Erlandsson, & Falk, 2016;Salazar & Meil, 2009), concrete could conceivably be a better solution in cases where it is produced with a low clinker content or carbon storage techniques (De Schepper, Van den Heede, Van Driessche, & De Belie, 2014;Razi, Razak, & Khalid, 2016). On the other hand, performance requirements allow for flexibility and innovation and ensure that the desired outcome is reached, but their implementation and monitoring often require dedicated software, staff training or third party experts.…”
mentioning
confidence: 99%
“…In an assessment of functionally equivalent concrete and timber designs for a small road bridge in Sweden, the timber bridge had a 22% lower EC [23]. Taking a similar approach to residential buildings, a cradle-to-grave LCA result for a CLT-based home had 42% lower EC than its concrete counterpart [24]. In both studies, the superiority of the timber variant was confirmed within parallel assessments using dynamic LCA.…”
Section: Lcas Of Buildings Using Timber Structuresmentioning
confidence: 84%
“…as a fast and cost-efficient building methodology [13], [14]. Wood is one of the most durable construction materials based on its renewability, ability to bind CO2 and requires a limited amount of energy during processing [5]. Further, wood has a relatively low density in comparison with concrete or steel, which allows for the transport of larger volumes, which is beneficial for industrial construction and the environment due to the reduced transport requirement [15].…”
Section: Review Of the Conceptual Frameworkmentioning
confidence: 99%
“…Building houses in renewable materials such as wood is beneficial from an environmental perspective. However, Life Cycle Analysis (LCA) analyses are not normally used in the industry, disregarding the positive effects of wood as a construction material [5]. However, wooden multi-family houses are being built to a greater extent than previously due to the support of new technologies.…”
Section: Introductionmentioning
confidence: 99%